EMPI: Enhanced Message Passing Interface in Modern C++ - Beni, Majid Salimi; Crisci, Luigi; Cosenza, Biagio (2023 IEEE/ACM 23rd International Symposium on Cluster, Cloud and Internet Computing (CCGrid), 2023)
Message Passing Interface (MPI) is a well-known standard for programming distributed and HPC systems. While the community has been continuously improving MPI to address the requirements of next-generation architectures and applications, its interface has not substantially evolved. In fact, MPI only provides an interface to C and Fortran and does not support recent features of modern C++. Moreover, MPI programs are error-prone and subject to different syntactic and semantic errors. This paper introduces EMPI, an Enhanced Message Passing Interface based on modern C++, which is directly mapped to the OpenMPI implementation and exploits modern C++ for safe and efficient distributed programming. EMPI proposes novel C++RAII-based semantics and constant specialization to prevent error-prone code patterns such as parameter mismatch, and reduce the overhead of handling multiple objects and perinvocation time. Consequently, EMPI programs are safer: six out of nine well-known MPI error patterns do not occur while correctly using EMPI semantics. Experimental results on five microbenchmarks and two applications on a large-scale cluster using up to 1024 processes show that EMPI's performance is very similar to native MPI and considerably faster than the MPL C++ interface.